Holocene mountain glacier history in the Sukkertoppen Iskappe area, southwest Greenland - Schweinsberg, Avriel D.; Briner, Jason P.; Miller, Gifford H.; Lifton, Nathaniel A.; Bennike, Ole; Graham, Brandon L. (Quaternary Science Reviews, 2018)
Mountain glaciers and ice caps (GIC) independent of the Greenland Ice Sheet respond rapidly to climate variations and records of their past extent provide information on the natural envelope of climate variability. Here, we use a multi-proxy approach that combines proglacial lake sediment analysis, cosmogenic nuclide surface-exposure dating (in situ 10Be and 14C), and radiocarbon dating of recently ice-entombed moss to generate a centennial-scale record of Holocene GIC fluctuations in southwestern Greenland. Following local deglaciation ∼10-9 ka, sediments from proglacial Crash Lake record a glacier advance at ∼9 ka that is indistinguishable from nearby ice sheet moraines, implying a synchronous response of GIC and the Greenland Ice Sheet to a centennial-scale climate event. Following this local glacier advance, GIC experienced net recession until ∼4.6 ka. Radiocarbon ages of in situ moss (n = 29) and Crash Lake sediments reveal intervals of glacier expansion at ∼1.8, 1.2 and 0.7 ka that are superimposed on an overall trend of net glacier expansion throughout the late Holocene. In situ 14C concentrations from bedrock adjacent to radiocarbon-dated moss samples further constrain the duration of ice cover through the Holocene in this region. We find that our glacier-size proxy records during the past ∼4 ka are broadly consistent with relatively lower temperatures recorded in GISP2 and occur during, or following, intervals of volcanic perturbations. Thus, we speculate that volcanic activity, although less frequent and intense than in the early Holocene and during the Little Ice Age, may have led to centennial-scale variability imprinted on net glacier expansion due to decreasing summer insolation through the late Holocene.
Keywords: Cosmogenic in situ 14C; Glacier fluctuations; Greenland; Holocene; lake sediment; Neoglaciation

Local glaciation in West Greenland linked to North Atlantic Ocean circulation during the Holocene - Schweinsberg, Avriel D.; Briner, Jason P.; Miller, Gifford H.; Bennike, Ole; Thomas, Elizabeth K. (Geology, 2017)
Recent observations indicate that ice-ocean interaction drives much of the recent increase in mass loss from the Greenland Ice Sheet; however, the role of ocean forcing in driving past glacier change is poorly understood. To extend the observational record and our understanding of the ocean-cryosphere link, we used a multi-proxy approach that combines new data from proglacial lake sediments, C-14-dated in situ moss that recently emerged from beneath cold-based ice caps, and Be-10 ages to reconstruct centennial-scale records of mountain glacier activity for the past similar to 10 k. y. in West Greenland. Proglacial lake sediment records and C-14 dating of moss indicate the onset of Neoglaciation in West Greenland at ca. 5 ka with substantial snowline lowering and glacier expansion at ca. 3.7 ka followed by additional ice expansion phases at ca. 2.9, ca. 1.7, and ca. 1.4 ka and during the Little Ice Age. We find that widespread glacier growth at ca. 3.7 ka in West Greenland coincides with marked cooling and reduced strength of the West Greenland Current in Disko Bugt. The transition to cooler ocean conditions at ca. 3.7 ka identified in Disko Bugt is registered by marine proxy data farther afield in East Greenland and on the northwestern Icelandic shelf, implying large-scale paleoceanographic changes across the North Atlantic during this interval. The similarity between glacier change on West Greenland and multiple marine and terrestrial records across the North Atlantic suggests that glaciers are strongly influenced by changes in ocean circulation and consequently implies that the ocean-cryosphere teleconnection is a persistent feature of the Arctic system.